Impact and oxidation of single silver nanoparticles at electrode surfaces: one shot versus multiple events. Issue 3 (20th December 2016) - Ustarroz, Jon; Kang, Minkyung; Bullions, Erin; Unwin, Patrick R.
Abstract : High bandwidth-low noise measurements of the electrochemical oxidation of individual silver nanoparticles (NPs) impacting on electrodes reveals the process to typically occur in a series of 'bites' (partial NP dissolution) rather than in a single shot, with the resulting current–time traces revealing considerable information on NP activity and transport near electrodes. Abstract : Single nanoparticle (NP) electrochemical impacts is a rapidly expanding field of fundamental electrochemistry, with applications from electrocatalysis to electroanalysis. These studies, which involve monitoring the electrochemical (usually current–time, I – t ) response when a NP from solution impacts with a collector electrode, have the scope to provide considerable information on the properties of individual NPs. Taking the widely studied oxidative dissolution of individual silver nanoparticles (Ag NPs) as an important example, we present measurements with unprecedented noise (< 5 pA) and time resolution (time constant 100 μs) that are highly revealing of Ag NP dissolution dynamics. Whereas Ag NPs of diameter, d = 10 nm are mostly dissolved in a single event (on the timescale of the measurements), a wide variety of complex processes operate for NPs of larger diameter ( d ≥ 20 nm). Detailed quantitative analysis of the I – t features, consumed charge, event duration and impact frequency leads to a major conclusion: Ag NPs undergo sequential partial stripping (oxidative dissolution) events, where a fraction of a NP is electrochemically oxidized, followed by the NP drifting away and back to the tunnelling region before the next partial stripping event. As a consequence, analysis of the charge consumed by single events (so-called "impact coulometry") cannot be used as a general method to determine the size of colloidal NPs. However, a proper analysis of the I – t responses provides highly valuable information on the transient physicochemical interactions between NPs and polarized surfaces.